Desobediência civil e a dimensão política da cidadania - Zappelini, Thaís Duarte (2018)
The present work aims to develop a critical and deductive analysis, from the perspective of the Philosophy of Law, of civil disobedience from its origins in the right of resistance and the safeguard of freedom, approaching the context that would conform it to the liberal molds. It is argued that civil disobedience is a popular mechanism for controlling legality, presenting a strict link with the political dimension of citizenship. Its role in the current political debate and its construction was based on the delimitation of State power through the building of the modern State and the contestation of monarchical Absolutism, at which point the citizen figure gained new meanings. The emblematic discussion of the concepts of negative freedom and positive freedom between liberal and republican theorists was treated by connecting freedom to its greatest antithesis: slavery. Hence, the hegemonic theorizations of disobedience and the potentially modifying republican propositions were discussed. Finally, the scenario of the Atlantic Revolutions and the primacy of the law they erected were examined, exploring some of the legal documents of the period that dealt with disobedience, arguing about legal civil disobedience as a positive expression of the right of resistance and seeking alternatives to the implementation of the civic participation in Contemporaneity.